Traffic Rule Awareness Among Bachelor-Level Two-Wheeler Riders in Kathmandu - Devkota, Isha; Chaulagain, Indira Kumari (ILAM इलम, 2025)
Traffic rules are planned to expedite the flow of traffic and prevent collisions among traffic. These road rules are important as they help in preventing crashes. Most traffic rules are for everyone’s safety. But still, road traffic injuries and accidents remain an important public health problem at global and national levels. The objective of this study was to find out the awareness level of traffic rules among bachelor-level two-wheeler rider students. A descriptive cross-sectional study was conducted in which 400 two-wheeler riders were selected among bachelor-level students from colleges of ward number seven of Kathmandu Metropolitan City. A self-administered pre-tested and reverse-translated questionnaire was used. Data were entered and analysed in the IBM SPSS 20.0 version. There were 78.2% male and 21.8% female riders of two-wheelers. Of the participants, 85.8% were more than 23 years of age, and the rest 14.2% were less. The study found that 51.5% of participants exhibited adequate awareness of traffic rules while 48.5% exhibited inadequate awareness. There was a significant association between the level of awareness of traffic rules with years of bachelor’s education, past experience of accidents, and the presence of a license. This study revealed the existence of inadequate knowledge of traffic rules among bachelor-level two-wheeler rider students. This suggests a need to design and implement a regular road safety campaign for these two-wheeler riders.